Assistance for Pregnant Women in Preventing KEK and Anemia - Farida Yuliani; Erfiani Mail; Fitria Edni Wari (STIKes Patria Husada Blitar, 2023)
Anemia in pregnant women is a health problem related to its high incidence and the complications that can arise in the mother and fetus. This community service aimed to provide assistance and counseling in the prevention of anemia and KEK in pregnant women so that pregnant women in the Gayaman Village area routinely consume FE tablets to prevent anemia. The method used mentoring and measuring the discipline in consuming FE tablets with a checklist and interviews about the regularity of FE tablet consumption. This community service was conducted on 25 pregnant women in September 2022-January 2023. The results revealed that based on interviews before the service was carried out, pregnant women still did not routinely consume FE tablets and did not pay attention to diets during pregnancy. After the explanation and assistance, pregnant women understood the benefits of consuming FE tablets regularly. Assistance needs to be given to pregnant women so that FE consumption is carried out regularly so that pregnant women avoid anemia and KEK.